The Effect Of Organizational Culture And Servant Leadership On Employee Performance Mediated By Organizational Commitment - Achmat Rofik; Lie Liana (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of organizational culture and servant leadership on employee performance mediated by organizational commitment. This study uses a quantitative approach. The population in this study were 78 State Civil Apparatus at the Regional Financial, Revenue, and Asset Management Agency of Batang Regency. Data were collected through questionnaires and analyzed using SPSS software version 24. Data analysis techniques include descriptions of respondents and variables, validity tests, reliability tests, F tests, R2 tests, t tests, and Sobel tests. The results show that organizational culture has a positive effect on organizational commitment, servant leadership has no effect. organizational commitment, organizational culture has a positive effect on employee performance, servant leadership has no effect on employee performance, and organizational commitment has a positive effect on employee performance. In addition, organizational commitment mediates the influence of organizational culture on employee performance and organizational commitment does not mediate the influence of servant leadership on employee performance..